Unequal Exchange of Air Pollution and Economic Benefits Embodied in China's Exports - Zhang, Wei; Wang, Feng; Hubacek, Klaus; Liu, Yu; Wang, Jinnan; Feng, Kuishuang; Jiang, Ling; Jiang, Hongqiang; Zhang, Bing; Bi, Jun (Environmental science & technology, 2018)
As the world's factory, China has enjoyed huge economic benefits from international export but also suffered severe environmental consequences. Most studies investigating unequal environmental exchange associated with trade took China as a homogeneous entity ignoring considerable inequality and outsourcing of pollution within China. This paper traces the regional mismatch of export-induced economic benefits and environmental costs along national supply chains by using the latest multiregional input-output model and emission inventory for 2012. The results indicate that approximately 56% of the national GDP induced by exports has been received by developed coastal regions, while about 72% of air pollution embodied in national exports, measured as aggregated atmospheric pollutant equivalents (APE), has been mainly incurred by less developed central and western regions. For each yuan of export-induced GDP, developed regions only incurred 0.4-0.6 g APE emissions, whereas less developed regions from western or central China had to suffer 4-8 times the amount of emissions. This is due to poorer regions providing lower value added and higher emission-intensive inputs and having lower environmental standards and less efficient technologies. Our results may pave a way to mitigate the unequal relationship between developed and less developed regions from the perspective of environment-economy nexus.
Keywords: Socioeconomic Factors; China; Čína; znečištění ovzduší; socioekonomické faktory; Environmental Pollution; znečištění životního prostředí; Air Pollution